Pro-environmental behavior in tourism and hospitality: science mapping of present and future trends - Muhammad Ashraf, Fauzi; Han, Heesup; Mohd Hafiz, Hanafiah; Noor Akma, Abu Bakar (Taylor & Francis, 2023)
This study evaluates the knowledge structure of pro-environmental behavior in the tourism and hospitality industry. Two bibliometric analyses explore current and emerging themes through bibliographic coupling analysis and co-word analysis. Findings depict that the current and emerging streams in pro-environmental behavior are primarily associated with the determinants of tourists’ behavior. The future streams suggest that themes are related to driving pro-environmental behavior through attitudes, values, norms and the development of satisfaction and loyalty. The implications of this study are relevant to stakeholders, operators, and destination practitioners to encourage and promote pro-environmental behavior as part of sustainability development initiatives.